The Essence and Structure of Economic Competence of Staff Officers of the State Border Guard Service of Ukraine - LevchukNataliіa (Pedagogical Discourse, 2016)
The article investigates the problems of staff officers’ economic competence of the State Border Guard Service of Ukraine during the professional training. The analysis of main approaches to the scientific concept of «competence» and «economic competence» has been provided. The importance of economic competence in the structure of border guards’ professional readiness as future leaders has been specified. Based on the view of scientists’ analysis about the nature of economic competence and according to specific economic activities by the State Border Guard Service of Ukraine staff officer the definition of the economic competence has been offered. The State Border Guard Service of Ukraine staff officer’s economic competence structure has been grounded and the following components have been characterized: the basis motivational component comprises stable and professional motives concerning the effective management of financial and economic activity ensuring, cognitive interest on the planning, organization, coordination and control specifics; cognitive component includes a system of economic knowledge, elements of which are knowledge of the budget system of Ukraine, organization and management of financial and economic activity in the State Border Guard Service of Ukraine and conducting inspections of financial and economic activities of the Agency; operating components are presented in skills and habits system that ensures successful implementation and decision-making in the field of financial and economic activities of the State Border Guard Service of Ukraine; personal component as a set of specific personal qualities that favorably affect the decision-making technology in the field of financial and economic activity. Key words: competence, economic competence, staff officer of Border Guard unit, structure, components.